2013
DOI: 10.1038/bjc.2013.681
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction of novel lactate dehydrogenase inhibitors with gemcitabine against pancreatic cancer cells in hypoxia

Abstract: Background:Hypoxia is a driving force in pancreatic-ductal-adenocarcinoma (PDAC) growth, metastasis and chemoresistance. The muscle-isoform of lactate dehydrogenase (LDH-A) constitutes a major checkpoint for the switch to anaerobic glycolysis, ensuring supply of energy and anabolites in hypoxic-environments. Therefore, we investigated the molecular mechanisms underlying the pharmacological interaction of novel LDH-A inhibitors in combination with gemcitabine in PDAC cells.Methods:Lactate dehydrogenase A levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 59 publications
3
124
0
Order By: Relevance
“…The effects of Gal-4 on migration and invasion were evaluated as described previously [40]. Migration was investigated using the LeicaDMI300B (Leica) migration station integrated with the Scratch-Assay 6.1 software (Digital-Cell Imaging Labs, Keerbergen, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of Gal-4 on migration and invasion were evaluated as described previously [40]. Migration was investigated using the LeicaDMI300B (Leica) migration station integrated with the Scratch-Assay 6.1 software (Digital-Cell Imaging Labs, Keerbergen, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, some of them demonstrate high potential in combination with current therapies. It was recently showed that NHI-1 and -2 used together with gemcitabine enhanced the antiproliferative and anti-invasive activities of the chemotherapeutic drug, under both normoxia and hypoxia, in pancreatic ductal adenocarcinoma (PDAC) cell lines [85]. It was also found that NIH-2, combined with the redox-dependent bioreductive anticancer prodrug EO9, synergistically induced p53-positive cancer cell death [86].…”
Section: Synthetic Ldh-5 Inhibitors and Their Therapeutic Potentialmentioning
confidence: 99%
“…Small molecules named as NHI derivatives N-hydroxyindole derivatives endowed strong synergistic inhibitory effect on both enzyme as well as cell-based assays and also inhibited spheroid growth, cell migration and invasion in pancreatic cancer cells in combination with gemcitabine. These results offer a new hope in the development of new potent hLDH-5 inhibitors and their utilization in combination therapy for cancer treatment [12]. Very recently, the role and therapeutic potential of hLDH-5 enzyme in brain tumors has been investigated and found significant involvement of hLDH-5 in brain tumors and glioblastoma multiform.…”
mentioning
confidence: 88%